The Celebration of Life’s Milestones and Significant Events: A Course-Based Qualitative Inquiry into Milieu Relational Work in Child and Youth Care Residential Programs - Bellefeuille, Gerard (Advances in Social Sciences Research Journal, 2021)
There has been little focus on the milieu relational work in child and youth care (CYC) residential programs for children and youth specific to the celebration of life’s milestones and events. The goal of this course-based study is to improve understanding of how CYC practitioners initiate and celebrate milestones and significant events with children and youth in care. The study uses interpretivism to identify and understand phenomena from the perspective of the individuals who have direct experience of the phenomena under investigation. Data was collected using an anonymous Google forms questionnaire. An interpretive thematic analysis of the data revealed four themes: (1) quality time with loved ones, (2) importance of acknowledgement (e.g., of youth’s wants and needs), (3) awareness of implementing culture, and (4) building connections and creating memories.